2014
DOI: 10.1111/dech.12080
|View full text |Cite
|
Sign up to set email alerts
|

Borrowing Across Borders: Migration and Microcredit in Rural Cambodia

Abstract: This article explores an unexpected and overlooked consequence of the expansion of microcredit: how it interacts with migration patterns. Drawing on qualitative research in northwest Cambodia, this study explores the uses, meanings and implications of ‘migra‐loans’ — microcredit loans that are used in tandem with household strategies of international migration. Using microcredit in combination with migration allows households to immediately meet consumption goals and utilize the credit being actively promoted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
46
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 23 publications
(24 reference statements)
0
46
0
Order By: Relevance
“…First, qualitative research has documented that households use formal loans to finance the costs of migration, a pattern that has been documented in Cambodia and in other microfinance-saturated communities (Chan and So 1999;Stoll 2010;Bylander 2014). While bank and MFI policies in Cambodia generally do not support loans to be used to finance migration, in areas where migration is common, loan officers have noted that loans have been used to cover migration costs (Bylander 2014). Second, households with relatives already away and regularly remitting may view formal credit as an advance on remittances to come, a pattern which has also been identified both within and outside of Cambodia (Duffy-Tumasz 2009;Bylander 2014).…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…First, qualitative research has documented that households use formal loans to finance the costs of migration, a pattern that has been documented in Cambodia and in other microfinance-saturated communities (Chan and So 1999;Stoll 2010;Bylander 2014). While bank and MFI policies in Cambodia generally do not support loans to be used to finance migration, in areas where migration is common, loan officers have noted that loans have been used to cover migration costs (Bylander 2014). Second, households with relatives already away and regularly remitting may view formal credit as an advance on remittances to come, a pattern which has also been identified both within and outside of Cambodia (Duffy-Tumasz 2009;Bylander 2014).…”
Section: Discussionmentioning
confidence: 96%
“…Second, households with relatives already away and regularly remitting may view formal credit as an advance on remittances to come, a pattern which has also been identified both within and outside of Cambodia (Duffy-Tumasz 2009;Bylander 2014). Qualitative research on microcredit in the Cambodian context has suggested that use of formal credit, and the resulting indebtedness, can lead to distress migration (Ovesen et al 2014;Bylander 2014). Among surveys of microfinance clients in credit-saturated areas in Cambodia, the migration of a family member was noted as a key way that households cope with overindebtedness (Liv 2013).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations